Omar Bin Al-khattab’s Policy In Confronting Pandemics And The International Economics Decisions - Abd Alkareem K. A. Eleyan; Mesbahul Hoque (USIM, 2024)
Al-Qanatir: International Journal of Islamic Studies, Volume 32 Issue 2, Page (294–310)